2022
DOI: 10.3390/ani12223166
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Sequencing Analysis of circRNA in Skeletal Muscle between Fast- and Slow-Growing Chickens at Embryonic Stages

Abstract: Skeletal muscle growth has always been the focus of the broiler industry, and circRNAs play a significant role in this process. We collected leg muscles of slow- and fast-growing Bian chicken embryos in the study at 14 (S14 and F14) and 20 (S20 and F20) days for RNA-seq. Finally, 123 and 121 differentially expressed circRNAs (DECs) were identified in S14 vs. F14 and S20 vs. F20, respectively. GO enrichment analysis for DECs obtained important biological process (BP) terms including nicotinate nucleotide biosyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…These primers were synthesized by Sangon (Shanghai, China). The qPCR experiments were conducted on Applied Biosystems 7500 (ABI, Los Angeles, California, USA) using SYBR qPCR Master Mix (Vazyme, Nanjing, China), and β-actin was used as housekeeping gene [46], with three technical repetitions for each sample. The 2 −∆∆CT method was used to calculate the relative expression of KLFs [47].…”
Section: Rna-seq Results Analysis Of the G Gallus Klf Genesmentioning
confidence: 99%
“…These primers were synthesized by Sangon (Shanghai, China). The qPCR experiments were conducted on Applied Biosystems 7500 (ABI, Los Angeles, California, USA) using SYBR qPCR Master Mix (Vazyme, Nanjing, China), and β-actin was used as housekeeping gene [46], with three technical repetitions for each sample. The 2 −∆∆CT method was used to calculate the relative expression of KLFs [47].…”
Section: Rna-seq Results Analysis Of the G Gallus Klf Genesmentioning
confidence: 99%
“…The RNA-seq results showed that the body weight differences between XH and WRR chicken are mainly reflected in metabolism, catalytic activity, and fatty acid metabolism according to the GO term and KEGG pathway analysis ( Figures 2 C– 2 D). Studies have shown that the weight difference of poultry after birth is mainly manifested in energy metabolism ( Kong et al, 2017 ), the host genes of differentially expressed circRNAs in late embryonic stage of slow- and fast-growing chicken muscle were also mainly enriched in metabolic pathways ( Zhang et al, 2022 ), proved that the difference in metabolic levels before and after birth is an important reason for the differences in muscle mass and growing speed in poultry.…”
Section: Discussionmentioning
confidence: 99%
“…We use the intersection of circRNA predicted by find_circ and CIRC software can improve the accuracy of circRNA. This method has been used in mice [ 52 ], cattle [ 53 ], sheep [ 54 ], chicken [ 55 ] and other species [ 56 ]. We identified a total of 16,990 expressed circRNAs, which is much higher than the number reported in one recent study.…”
Section: Discussionmentioning
confidence: 99%